What Is the Main Cause of Diurnal Variation and Nocturnal Peak of Summer Precipitation in Sichuan Basin, China? The Key Role of Boundary Layer Low‐Level Jet Inertial Oscillations. Issue 5 (14th March 2019) - Zhang, Yuehan; Xue, Ming; Zhu, Kefeng; Zhou, Bowen
Abstract: The precipitation in Sichuan Basin (SB), China, exhibits pronounced diurnal variation, including minimum rainfall in daytime and a prominent peak near midnight. This study investigates the primary mechanism of precipitation diurnal variation in SB using forecasts from three summer months of 2013 produced at a 4‐km grid spacing. The model forecasts reproduce the observed spatial distributions and diurnal cycles well, including the peak precipitation in SB at around 02 local solar time (LST). Contrary to the common belief that emphasizes the solenoidal effects associated with the Tibetan and Yunnan‐Guizhou Plateaus, prominent diurnal inertial oscillations of boundary layer south‐southwesterly low‐level jet into SB are shown to play more important roles in modulating the diurnal cycles of precipitation in SB. A basinwide moisture budget analysis is performed to reveal that the moisture flux from the southeast side of the basin dominates within the diurnal oscillations of the net moisture flux into the basin, and the much enhanced nocturnal low‐level jet plays a crucial role in the formation of nocturnal precipitation within the basin. The net moisture flux into SB reaches maximum at around 22 LST, the time boundary layer perturbation winds from the daily mean in the direction normal to the southeastern boundary of SB reach maximum, which is about 4 hr before precipitation peak at around 02 LST. Shallow thermally forced nighttime downslope flows and daytime upslope flows on the Tibetan Plateau and Yunnan‐Guizhou Plateau slopes contribute only a small portion of moisture fluxes through the basin boundaries. Key Points: The diurnal cycles of summer precipitation, including the prominent peak shortly after midnight, are reproduced well by 4‐km forecasts The diurnal variations of the southerly low‐level jet are found to play dominant roles in controlling the precipitation diurnal cycles The diurnal variations of low‐level jet can be explained well by the boundary layer inertial oscillations theory of Blackadar